On the oscillation of Caputo fractional differential equations with Mittag–Leffler nonsingular kernel. (October 2019) - Abdalla, Bahaaeldin; Abdeljawad, Thabet
Abstract: In this article, we derive sufficient conditions to prove the oscillation for solutions of Caputo fractional differential equations with Mittag–Leffler nonsingular kernel of the form ( a A B C D κ 0 ξ ) ( t ) + ϕ 1 ( t, ξ ) = θ ( t ) + ϕ 2 ( t, ξ ), t > a ξ k ( a ) = b k ( k = 0, 1, …, n ), where n < κ 0 ≤ n + 1 and a A B C D κ 0 is the left-fractional Caputo derivative with Mittag–Leffler nonsingular kernel or the Atangana–Baleanu fractional derivative in the sense of Caputo. An example is given to validate part of the proven results.,